Rapid and nondestructive estimations of chlorophyll concentration in date palm (Phoenix dactylifera L.) leaflets using SPAD-502+ and CCM-200 portable chlorophyll meters - Almansoori, Thuraya; Salman, Majeda; Aljazeri, Mariam (Emirates Journal of Food and Agriculture, 2021)
Date palm (Phoenix dactylifera L.) is the oldest known tree grown in the world’s arid regions. It has been cultivated for centuries because of its enormous cultural, agricultural, and environmental benefits. Recently date palm groves have been declined drastically due to anthropogenic, abiotic and, biotic stresses. Attaining sustainable farming and optimum crop production requires frequent monitoring of the physiological status of date palms. This demands rapid and non-destructive estimation of chlorophyll concentration in date palm leaflets overtime. In this study, four date palm cultivars, exhibiting distinct concentrations of chlorophyll, were used to assess the potential of using SPAD-502+ and CCM-200 portable chlorophyll meters to estimate the concentration of chlorophyll in date palm leaflets. Regression analyses were performed to model the relationship between the absolute concentration of chlorophyll measured in vitro and the optic indices of the two portable chlorophyll meters (SPAD and CCI). The results revealed that polynomial and power prediction models, which demonstrated remarkably close fits to each another, are the best functions to parameterize the relationships. The calibration models developed in this study were very strong and recorded high coefficient of determinations along with low relative errors for both the cultivar-specific fits (R2 ≥ 0.89; Error % ≤ 18.3) as well as the generic species-specific fits (R2 ≥ 0.822; Error % ≤ 25.0). The results confirmed that both SPAD-502+ and CCM-200 are equally effective tools for rapid and nondestructive estimation of chlorophyll concentration in date palm leaflets.